2019
DOI: 10.1186/s12884-019-2465-6
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and determinants of essential neonatal care utilization among underprivileged ethnic groups in Midwest Nepal: a mixed method study

Abstract: Background Globally in 2017 neonatal death accounted for 46% of under-five deaths. Nepal is among the developing countries which has a high number of neonatal deaths. The rates are high among poor socio-economic groups, marginalized, as well as people living in remote areas of Nepal. This paper, thus tries to examine the utilization pattern and maternal, household, and health service factors affecting underprivileged ethnic groups in Midwest Nepal. Methods A cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
4
8
2
Order By: Relevance
“…Also, the proportion of sick newborns admitted in the hospital from multi-parous mother was higher after FNC than before implementation. This nding is similar with another study conducted in Nepal which reported that primiparous mothers have signi cant increment in neonatal care utilization in comparison to those of multiparous mothers [29].…”
Section: Discussionsupporting
confidence: 90%
“…Also, the proportion of sick newborns admitted in the hospital from multi-parous mother was higher after FNC than before implementation. This nding is similar with another study conducted in Nepal which reported that primiparous mothers have signi cant increment in neonatal care utilization in comparison to those of multiparous mothers [29].…”
Section: Discussionsupporting
confidence: 90%
“…Many cultural practices of advantageous groups like wrapping newborn with old clothes, applying oil to umbilical cord and poor breast feeding practices can result in neonatal infection. A study in a rural Nepal showed that the level of awareness among disadvantageous group is better than advantageous ethnic group [30].…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 16 full-text articles were assessed for eligibility criteria based on the pre-defined criteria. Among these five articles were further excluded due to they are not inline to the preset criteria, three studies from Ethiopia [20][21][22], one study from Nepal [23] and one study from Himalayas [24]. Finally, 11 studies fulfilled the eligibility criteria and included in this systematic review and meta-analysis ( Fig.…”
Section: Study Selection and Data Extractionmentioning
confidence: 99%